Cross‐platform comparison of next‐generation sequencing and matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry for detecting KRAS/NRAS/BRAF/PIK3CA mutations in cfDNA from metastatic colorectal cancer patients. Issue 9 (17th August 2021) - Xu, Xiaojing; Huang, Fei; Cao, Minlu; Chen, Xinning; Wang, Hao; Jiang, Huiqin; Yu, Yiyi; Shen, Minna; Yang, Yihui; Wang, Beili; Liu, Tianshu; Guo, Wei
Abstract: Background: Examining tumor KRAS/NRAS/BRAF/PIK3CA status in metastatic colorectal cancer (mCRC) is essential for treatment selection and prognosis evaluation. Cell‐free DNA (cfDNA) in plasma is a feasible source for tumor gene analysis. Methods: In this study, we recruited mCRC patients and analyzed their KRAS/NRAS/BRAF/PIK3CA status in cfDNA using two platforms, next‐generation sequencing (NGS) and matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF). The performance between the two platforms and the concordance rate between cfDNA and tissue were analyzed. The relationship between cfDNA‐related variables and clinical variables was also assessed. Tumor mutations in cfDNA from patients receiving continuous treatments were monitored in the follow‐ups. Results: Next‐generation sequencing and MALDI‐TOF had similar specificity (100.0% vs. 99.3%) and negative predictive value (99.9% vs. 99.4%), whereas NGS had higher sensitivity (97.1% vs. 85.3% of MALDI‐TOF) and positive predictive value (100% vs. 82.9% of MALDI‐TOF). The overall concordance rate of NGS and MALDI‐TOF was 98.6%. For the reportable types of mutations in both cfDNA and tissue, the concordance rate was 96.1%. Among 28 tissue‐positive patients, the allele frequencies of tumor mutations in cfDNA were higher in patients with primary tumor burden ( p  = 0.0141). Both CEA and CA 19‐9 were positively correlated with cfDNA concentration ( r  = 0.3278 and r  = 0.3992). The allele frequencies of tumor mutations changed with disease progression. Conclusions: Next‐generation sequencing showed slightly better performance in detecting cfDNA mutations and was more suitable for clinical practice. cfDNA‐related variables reflected the tumor status and showed a promising potential in monitoring disease progression. Abstract : Nowadays, liquid biopsy using plasma cell‐free DNA (cfDNA) is a crucial tool in cancer management. But it is still confusing which platform should be used as well as how to use cfDNA. In this study, we conducted a prospective study to compare two broad‐coverage profiling platforms, next‐generation sequencing (NGS) and matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF), on cfDNA analysis and explore the potential use of cfDNA in metastatic colorectal cancer (mCRC). Our results revealed the advantages of NGS assay over MALDI‐TOF assay and indicated how to improve MALDI‐TOF assay. Moreover, our results suggested the potential value of cfDNA analysis in monitoring treatment response in mCRC.